Hands up, don't shoot: why the protests in Ferguson and Baltimore matter, and how they changed America - Cobbina-Dungy, Jennifer (New York University Press, 2019)
Introduction -- Race & policing: the more things change, the more they remain the same -- "Guilty until proven innocent": life under suspicion -- "It's a blue thing": race and black police officers -- "We stand united": why protesters marched -- "I will be out here every day strong!" : repressive policing and future activism -- Public disorder -- Conclusion